Studies on seasonal variation in the biochemical composition of the Indian shad, Tenualosa ilisha (Hamilton, 1822) - Majumdar, R K; Basu, S (Indian Journal of Fisheries, 2016)
An year round study on the macro and micro-nutrient constituents of the Indian shad (Tenualosa ilisha) was carried out. The average values of the proximate composition recorded were: moisture – 68.16%, ash – 1.42%, protein – 16.27%, fat – 12.04%, calcium – 55.09%, phosphorous – 184.58%, sodium – 66.10% and potassium – 179.95%. The summation of moisture and fat content was 80%. The correlation coefficient (r) between moisture and fat content obtained was – 0.987 indicating an inverse relationship. The correlation coefficients between weight and moisture and weight and fat content recorded were 0.670 and 0.7181 respectively. The maximum moisture content was observed in January (74.22%) when the average weight of the sample was 357.83 g and the minimum was found in September (58.82%) when the average weight of the sample was 788.35 g. The lowest fat content was recorded during January to April, whereas, the maximum fat content was found during July to September. In the rest of the period, the average fat content was 11.45 %. The proportion of calcium and phosphorous in the flesh of hilsa was found to increase with increase in size of the fish. On the other hand, sodium, the most vital tissue component of fish, decreased considerably with growth of the fish, whereas no definite trend of variation was observed in potassium content of the fish.